Correction of the valves insufficiency after performance of orthotopic transplantation of the heart - B. M. Todurov; G. I. Kovtun; O. A. Loskutov; D. O. Loskutov (Клінічна хірургія)
Correction of the valves insufficiency after performance of orthotopic transplantation of the heart